Diverse carrier mobility of monolayer BNCx: a combined density functional theory and Boltzmann transport theory study. (20th October 2017) - Wu, Tao; Deng, Kaiming; Deng, Weiqiao; Lu, Ruifeng
Abstract: BNC x monolayer as a kind of two-dimensional material has numerous chemical atomic ratios and arrangements with different electronic structures. Via calculations on the basis of density functional theory and Boltzmann transport theory under deformation potential approximation, the band structures and carrier mobilities of BNC x ( x = 1, 2, 3, 4) nanosheets are systematically investigated. The calculated results show that BNC2 -1 is a material with very small band gap (0.02 eV) among all the structures while other BNC x monolayers are semiconductors with band gap ranging from 0.51 eV to 1.32 eV. The carrier mobility of BNC x varies considerably from tens to millions of cm 2 V −1 s −1 . For BNC2 -1, the hole mobility and electron mobility along both x and y directions can reach 10 5 orders of magnitude, which is similar to the carrier mobility of graphene. Besides, all studied BNC x monolayers obviously have anisotropic hole mobility and electron mobility. In particular, for semiconductor BNC4, its hole mobility along the y direction and electron mobility along the x direction unexpectedly reach 10 6 orders of magnitude, even higher than that of graphene. Our findings suggest that BNC x layered materials with the proper ratio and arrangement of carbon atoms will possess desirable charge transport properties, exhibiting potential applications in nanoelectronic devices.